Bibliometric Mapping of Energy Literacy and Public Participation in Energy Transition: A Visual Analysis of Thematic Structure and Conceptual Linkages - Budiman, Rahmadi; Wardani, Dewi Kusuma; Hindrayani, Aniek; Sabandi, Muhammad (Universitas Sebelas Maret, 2025)
This study aims to map the thematic structure and conceptual linkages within the literature on energy literacy and public participation in the context of energy transition. Using a bibliometric approach, publication data were collected through an automated extraction process from open-access sources using a Python script designed to retrieve metadata from titles and abstracts. The analysis was conducted using the VOSviewer software to identify co-occurrence relationships among terms and to assess thematic relevance levels.The visualization results reveal two major clusters. The first cluster represents an educational approach, encompassing terms such as “energy literacy”, “student”, “curriculum”, and “pedagogy”. The second cluster reflects a participatory approach characterized by terms such as community, public participation, awareness, and project. The term “energy literacy” emerges as a central node connecting both clusters, indicating its strategic role in shaping public understanding and engagement with renewable energy issues. The findings contribute to strengthening conceptual understanding within the field of sustainable energy studies and open new opportunities for developing policy evaluations based on thematic data and bibliometric visualization.